A modernidade líquida e a descolonialidade plurinacional: uma análise sul-latino-americana do papel do século XXI - Silva, Heleno Florindo da (2019)
The present thesis seeks, from a methodological approach based on the dialectic of a Marxist nature and through a multiple-dialectical reflection, to use a possible answer to the questioning about the possibility of identifying, in the new Latin American constitutional trends (Global South) , now called the new constitutionalism - democratic, Andean, without parents - Latin American, as well as in the alternative presented by the Plurinational State model, as a hypothesis of the uncovering of diversity, an initial moment of rupture in the domains of liquidity of with the liberal-constitutional standard established by Modernity to the State, having the capacity to provide, as a consequence, a liberation movement of Being by establishing a decolonial role for the State in the 21st Century. In order to do so, attention was paid to the study of the epistemological-rational lines of construction of the national State, based on a debate on Modernity, the formation of the state model, and the importance of Capitalism for its expansion. they discussed, among other aspects, the medieval influences in the construction of the epistemological bases of the mentioned state premise, identified by the classic theories of state study, as of modern construction; the formation of the device vs. us. they by constructing a national identity as a modern aesthetic of the ascendant state, and in the end the rational premises behind the affirmation of capitalism through the liberal-market market system as one of the main modern foundations of the national state. The second part of the paper discusses net modernity and, from then on, the need to refound this state model in the 21st century, which is done through a closer analysis of the transformation of society and of the state itself into modern liquid times, as well as the debate inherent in consumerism, raised by the twentieth century, to the level of political, social, economic substratum - and, above all, necessary - to achieve happiness and, as a result of this context, the need of refounding the foundations on which the national state was built, in order, above all, to achieve liberation and disenfranchisement of the right to diversity. Finally, in the third and last part of this thesis, an analysis was made of the beginning of the end of the nation-state and the need to (re) think alternatives to the market-consumerist state as a means for us to change the reality of the present and future generations. This debate has taken place through the epistemological premises of intercultural decoloniality and the search for the unveiling of diversity in the 21st century as a way to achieve a new state rationality in a new century, and more, through an analysis of the new South-Latin constitutional trends as a kind of epistemological turning from the South, because we understand that this context marks the first alternative of rational rupture with the political-philosophical and socio-economic bases that sustain the modern national state.